PENGARUH PENAYANGAN FILM SPIRITUAL TERHADAP PERILAKU MORAL ANAK USIA 4-5 TAHUN DI TK EDUCATION 21 KULIM KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Riris Natalia Lubis; Zulkifli '; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims 1) To find a picture of the moral behavior of children aged 4-5 years in kindergarten Education 21 Kulim District of umbrellas Sekaki Pekanbaru Before being treated publishers spiritual movie. 2) To know the description of moral behavior of children aged 4-5 years in kindergarten Education 21 Kulim District of umbrellas Sekaki Pekanbaru After being treated publishers spiritual movie. 3) To know how much influence the film publishers spiritual to moral behavior aged 4-5 years in kindergarten Education 21 Kulim District of umbrellas Sekaki Pekanbaru. This type of research is an experimental research. Riduwan (2005) study with experimental approach is a study that is trying to find a particular referrer variable to another variable in strictly controlled conditions closely. The research sample that is child-Red K1 classes consisting of 18 children where 9 boys and 9 girls. Collecting data using observation and documentation. Based on the survey results revealed that 1) The ability of the moral behavior of children aged 4-5 years in kindergarten Education 21 Kulim District of umbrellas Sekaki Pekanbaru City before being given treatment in the form of a spiritual film screenings are low. 2Kemampuan moral behavior of children aged 4-5 years in kindergarten Education 21 Kulim District of umbrellas Sekaki Pekanbaru City after being given treatment in the form of a spiritual film screenings has increased and is high. 3) Advertising spiritual films have a significant effect on the ability of the moral behavior of children aged 4-5 years in kindergarten Education 21 Kulim District of umbrellas Sekaki Pekanbaru. It can be seen that there are differences related to increase the moral behavior of children before and after treatment. 4) Serving spiritual films have the effect of 29.40% against the ability of the moral behavior of children aged 4-5 years in kindergarten Education 21 Kulim District of umbrellas Sekaki PekanbaruKeywords: Film Spiritual, Moral Behavior, Children ages 4-5 years